UK bone conduction hearing device consensus workshop: Narrative summary†. (4th July 2017) - Mandavia, Rishi; Dimitriadis, Panagiotis A.; Monksfield, Peter; Hall, Amanda; Ray, Jaydip; Schilder, Anne G. M.
Abstract : Objectives : To identify United Kingdom (UK)-specific research priorities in the field of bone conduction hearing devices (BCHDs). Method : Narrative summary of the discussions and outcomes of a UK BCHD research workshop. The workshop was organized on 8 September 2016 under the auspices of the National Institute for Health Research (NIHR) Clinical Research Network (CRN) ENT Specialty group and Royal College of Surgeons (RCS) Clinical Research Initiative. Representatives from a wide range of patient and professional groups from the UK and abroad were invited to attend. Main outcome measures were research priorities and approaches in the field of BCHDs. Results : Key research questions in the field of BCHDs are as follows: (1) What are the existing national BCHD practices? (2) What are the patient information and support needs on BCHDs? (3) Which outcomes should be measured across clinical studies in the field of BCHDs? The workshop suggested the following approaches to address these priorities: (1) a service evaluation of current UK BCHD practice; development of a national registry of BCHDs; (2) qualitative research to understand patient information and support needs; development of patient decision support tools; (3) development of core outcome sets for BCHDs. Discussion : Building upon the framework of the recent UK Research Agenda for ENT, Hearing and Balance, patients and professionals defined key UK-specific research priorities and approaches in the field of BCHDs. This approach promotes engagement, buy-in, national collaboration and thereby value of future BCHD research.